Evaluation and Treatment of Alkalosis in Children - Kopač, Matjaž (Journal of Pediatric Intensive Care, 2019)
Alkalosis is a disorder of acid–base balance defined by elevated pH of the arterial blood. Metabolic alkalosis is characterized by primary elevation of the serum bicarbonate. Due to several mechanisms, it is often associated with hypochloremia and hypokalemia and can only persist in the presence of factors causing and maintaining alkalosis. Respiratory alkalosis is a consequence of dysfunction of respiratory system's control center. There are no pathognomonic symptoms. History is important in the evaluation of alkalosis and usually reveals the cause. It is important to evaluate volemia during physical examination. Treatment must be causal and prognosis depends on a cause.
Keywords: alkalosis; children; chloride